'Under the shade I flourish': an environmental history of northern Belize over the last three thousand five hundred years - Rushton, Elizabeth A.C. (2014)
Environmental histories are multi-dimensional accounts of human interaction with the environment over time. They observe how and when the environment changes (material environmental histories), and the effects of human activities upon the environment (political environmental histories). Environmental histories also consider the thoughts and feelings that humans have had towards the environment (cultural/ intellectual environmental histories). Using the methodological framework of environmental history this research, located in sub-tropical northern Belize, brings together palaeoecological records (pollen and charcoal) with archival documentary sources. This has created an interdisciplinary account which considers how the vegetation of northern Belize has changed over the last 3,500 years and, in particular, how forest resources have been used during the British Colonial period (c. AD 1800 – 1950). The palaeoecological records are derived from lake sediment cores extracted from the New River Lagoon, adjacent to the archaeological site of Lamanai. For over 3,000 years Lamanai was a Maya settlement, and then, more recently, the site of two 16th century Spanish churches and a 19th century British sugar mill. The British archival records emanate from a wide variety of sources including: 19th century import and export records, 19th century missionary letters and 19th and 20th century meteorological records and newspaper articles. The integration of these two types of record has established a temporal range of 1500 BC to the present. The palaeoecological proxies provide a low resolution record over a period of 3,500 years (c. 1500 BC – AD 2010) whereas the archival record provides annual resolution over a period of approximately 150 years (c. AD 1800 – 1950). This research also uses documentary sources to reconstruct temperature and precipitation for Belize City during the period 1865 – 2010, which is the first of its kind from Belize, and the oldest continuous record from Central America. It also provides the meteorological context for further exploration into British colonial interaction with ‘tropical’ climates. Perhaps because of its status as Britain’s only Central American colonial outpost, Belize has remained on the periphery of research concerning European interactions with tropical climates. This environmental history draws together a new account of health, place and space in the 19th century colonial tropics, drawing out how different understandings of the aetiologies and transmission of disease developed, in particular yellow fever. These different research strands are brought together to create an account that considers material, political and cultural aspects of environmental history. This has enabled the identification of eight phases of human interaction with the landscape at Lamanai, which are broadly indicative of general trends across northern Belize. These include the establishment of Maya field-based agriculture c. 1600 BC and a later phase of substantial Maya construction and site development c. 170 BC – AD 150. A period of active Maya management of forest, field, savanna and palm resources is also observed c. AD 500 – 1000. Polarised imaginings of the Maya as both destroyers and protectors of the tropical forest are challenged. Spanish interaction with the landscape is evident during c. AD 1500 – 1700 and this is followed by a period of substantial British colonial exploitation of timber resources, with logwood extracted c. AD 1660 – 1910 and mahogany extracted c. AD 1750 – 1945. These periods of extraction were only identifiable in the pollen record by combing the chronology from the documentary record with observed changes in the vegetation record and this demonstrates how these two contrasting methodologies can be usefully integrated. This environmental history rejects the binary opposition of benign, passive Maya landscapes and the violent, devastated European colonial landscape (Denevan, 1992). Analysis of the pollen and documentary records reveal that biodiversity is at the highest levels post AD 1950, which suggests that the forest can regrow even after multiple, diverse and prolonged periods of anthropogenic use in a matter of decades.